Pengetahuan, Sikap dan Perilaku Masyarakat dalam Melaksanakan Protokol Kesehatan Pencegahan COVID-19 - Naiyo Darafunna; Teuku Tahlil; Dini Mulyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the community's knowledge, attitudes, and behavior in implementing the COVID-19 prevention health protocol in Banda Aceh City. The type of research used is descriptive with a cross-sectional study design. The study results showed that public knowledge was excellent, as many as 237 (56.4%) people. As many as 322 (76.7%) people, Attitudes are included in the superb category. The community's behavior is as excellent as many as 299 (71.2%) people. Conclusions, knowledge, attitudes, and behavior in implementing the COVID-19 prevention health protocol in Banda Aceh City are in the excellent category. Keywords: COVID-19 Prevention, Knowledge, Behavior, Attitude